2020
DOI: 10.1111/jcpt.13306
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Drug Reactions Spontaneously Reported at a Tertiary Care Hospital and Preventable Measures Implemented

Abstract: What is known Limitations of clinical trials in determining all safety concerns related to a drug are well recognized. Monitoring spontaneous adverse drug reaction (ADR) reports remains an easy and relatively inexpensive method for overseeing that a drug remains a safe and effective option for patients. Objective To characterize and describe ADR reports at one of the largest healthcare institutions in the region and share the measures implemented by the team. Methods We conducted a retrospective analysis of al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…Abu Ebsa (2021) reported ADRs caused 1.6% resulted in hospital admission, 1.4% required intensive medical care and 0.3% of the reported ADRs caused permanent harm. 27 The occurrence of ADRs required early cessation of the causal drug, which worsened the disease condition. Factors such as dose-related and drug-related ADR are usually predictable but sometimes unavoidable.…”
Section: Discussionmentioning
confidence: 99%
“…Abu Ebsa (2021) reported ADRs caused 1.6% resulted in hospital admission, 1.4% required intensive medical care and 0.3% of the reported ADRs caused permanent harm. 27 The occurrence of ADRs required early cessation of the causal drug, which worsened the disease condition. Factors such as dose-related and drug-related ADR are usually predictable but sometimes unavoidable.…”
Section: Discussionmentioning
confidence: 99%
“…The ultimate goal of a hospital pharmacovigilance program is to improve medication safety and prevent harm. Despite the limitations of the spontaneous ADR reporting system, it is useful for monitoring internal trends and providing signals on drug safety that could be addressed through internal policies [ 46 ]. Some actions that could help improve drug safety in hospitals are aimed at promoting consultation with clinical pharmacologists for the evaluation and diagnosis of the causality of ADRs, monitoring of drug doses, safe prescription tools such as electronic prescriptions to assist in avoiding errors and drug interactions to prevent ADRs, double-checking the administration of risky medications, and having nurses with experience in working with hospitalized pediatric patients.…”
Section: Discussionmentioning
confidence: 99%
“… 19 Clinical trials identify adverse reactions of medications, but often, not all ADRs are known until medications are on the market, making ADR reporting crucial to improving patient care. 9 , 20 …”
Section: Introductionmentioning
confidence: 99%
“…Abu Esba et al 20 credit an increase in ADR reporting to more education and awareness surrounding the importance of reporting. This study finds that a third of the ADRs reported could have been avoidable, showing the importance of prevention efforts after an ADR is discovered.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation